2010
DOI: 10.1677/jme-10-0101
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a unique short form of the porcine prolactin receptor

Abstract: Prolactin (PRL) is required not only for maintenance of gestation in pigs but also for mammary gland development and subsequent lactogenesis. The actions of PRL are modulated by both long and short isoforms of the PRL receptor (PRLR), where short isoforms can interfere with the essential signaling function of the long isoform. Using 3 0 RACE we have isolated a unique splice variant of the porcine PRLR (pPRLR) that contains a short intracellular domain of 38 aa that is encoded by splicing from exon 9 to a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 56 publications
3
36
0
Order By: Relevance
“…1). The orientation and locations of exons 3 through 11 on the reverse strand of chromosome 16 were as described previously (Trott et al 2011), which are in accordance with the hPRLR gene that is located on the reverse strand of H. sapiens chromosome 5. From our annotation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). The orientation and locations of exons 3 through 11 on the reverse strand of chromosome 16 were as described previously (Trott et al 2011), which are in accordance with the hPRLR gene that is located on the reverse strand of H. sapiens chromosome 5. From our annotation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nulliparous Hampshire!Yorkshire female pigs (nZ11) were housed, killed and tissues sampled as described previously (Trott et al 2011). The pregnant pigs were unilaterally hysterectomised-ovariectomised and then killed at different stages of gestation, as described previously (Freking et al 2007, Trott et al 2009).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In peripheral sensory neurons, ASICs are detected in axons, axon terminals and cell bodies, where their activation contributes to pain signaling (Price et al, 2001). It has been shown that ASICs play an important role in various pain conditions such as inflammatory pain, postoperative pain and migraine (Deval et al, 2011;Kellenberger and Schild, 2015;Trott et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%